A compact dual‐band dual‐mode antenna for GPS L1/L2 adaptive interference cancellation. Issue 3 (22nd October 2019) - Rezazadeh, Navid; Shafai, Lotfollah
Abstract: A dual‐band dual‐mode microstrip antenna design is presented, with the application of adaptive interference cancellation in global positioning system at the L1 and L2 bands. The antenna consists of two stacked TM11 rings and two stacked TM21 shorted rings all fed by coaxial probes. By properly combining the two modes and utilizing both polarization components of each mode, up to three nulls can be steered at each frequency band to cancel interferers close to horizon. The concentric structure of the radiating patches in the proposed design allows for a compact antenna, which for a substrate of dielectric constant of 10 is only 0.33 λ in diameter at its lowest frequency of operation and can be further miniaturized on a higher dielectric constant substrate.